Відповідь:
Будь ласка зверніться до Пояснення.
Пояснення:
# "Необхідна умова:" P (AuuB) = P (A) + P (B) -P (AnnB) …. (зірка) #.
#P (AuuBuuC) = P (AuuD), "де," D = BuuC #, # = P (A) + P (D) -P (AnnD) ………. тому, що (зірка) #, # = P (A) + колір (червоний) (P (BuuC)) - колір (синій) (P Ann (BuuC)) #, # = P (A) + колір (червоний) (P (B) + P (C) -P (BnnC)) - колір (синій) (P (AnnB) uu (AnnC)), #
# = P (A) + P (B) + P (C) -P (BnnC) -колір (синій) {P (AnnB) + P (AnnC) -P ((AnnB) nn (AnnC) #, # = P (A) + P (B) + P (C) -P (AnnB) -P (BnnC) -P (AnnC) + P (AnnBnnC), #
за бажанням!